Digital Governance — Further Developing Economic Policy Based on Data and Evidence - Philipp Steinberg; Nils Börnsen; Dirk Neumann (Wirtschaftsdienst)
Abstract Digitalisation is bringing about far-reaching changes for the economy and society. Against this backdrop, the Federal Ministry for Economic Affairs and Energy published a concept paper for a regulatory action programme to support the digital transformation in December 2020 as part of the Federal Government’s implementation strategy “Shaping Digitalisation”. Its core thesis is that the basic ideas of regulatory policy remain valid in the digital economy. Its principles are still pillars of the social market economy today and can provide clear orientation for economic policy in the future in an increasingly digital economy. One of the paper’s approaches to the implementation of a digital regulatory policy is examined in more detail: the data- and evidence-based further development of economic policy.